횡령에 대한 합리적 과세방안에 관한 연구 - 김정애; 이영환 (의정논총, 15(2), 2020)
일반적으로 대표자가 해당 법인의 경제적 이익을 불법으로 횡령을 하는 경우, 대표자는 가해자가 되고, 법인은 피해자가 된다. 법인이나 대표자에 대한 과세문제를 검토할 때 적어도이러한 개념은 염두에 둘 필요가 있다. 그러나 현행 세법에는 피해자인 법인에게도 원천징수의무를 부담시키고 있다. 따라서 법인 대표자의 납세의무와 관련하여 법인에 대한 피해복구를 장려하고, 몰수·추징된 경우와의 형평성 측면에서 적어도 대표자가 회수 반환한 금액에대해서는 납세의무를 면제하는 방식으로 개선될 필요가 있다. 한편, 대표자가 경제적 이익을 자신에게 귀속시켰더라도 1인 주주의 지위에 의하여 뒷받침되지 않으면, 법인은 손해배상책임을 부담하므로 그러한 경제적 이익을 사실상 자신에게 귀속시킬 수 없다. 그러나 1인 주주이자 대표자는 자신의 횡령행위로 인한 손해배상책임을 자신의의사로 면제시킬 수 있기 때문에 이익을 자신에게 귀속시킬 수도 있다. 따라서 현행 세법에서‘상여’로 간주하고 있는 것을 미국처럼 ‘배당’으로 간주하는 방식으로 개선될 필요가 있다. 또한 법인에게 소득처분에 따른 원천징수의무를 부과하여 법인세 부담 외에 추가로 소득세 부담까지 가중시키고 있는 현행 세법은 하나의 횡령행위에 대해 법인에 대한 법인세 납세의무와 대표자에 대한 소득세 납세의무를 중복으로 부과하고 있다. 이는 이중과세에 해당할여지가 있으므로 관련 규정된 규정은 개정될 필요가 있다. If the representative illegally embezzles the economic interests of the corporation, the perpetrator becomes the representative and the victim becomes the corporation. At least these concepts need to be kept in mind when reviewing taxation issues for the legal entity or representative. Regarding the tax obligation of the representative of the relevant corporation, it should be improved by encouraging the restoration of damage to the corporation, and at least exempting the tax obligation for the amount recovered and returned by the representative in terms of maintaining equity with the case of confiscation or collection. Therefore, even if the representative attributed the economic interests to himself, if it is not supported by the status of a single shareholder, he or she bears the liability for damages to the relevant corporation, and such economic interests cannot be attributed to him. However, one-member shareholders and representatives can exempt their own liabilities for damages caused by embezzlement, so the profits can be attributed to them. Therefore, it is necessary not to view it as the current “bonus”, but as a “dividend” like the United States in principle. In addition, adding to the tax burden in addition to the corporate tax burden by imposing the withholding obligation on the relevant corporation according to the disposition of income corresponds to the double imposition of the corporate tax obligation and the representative's income tax obligation to pay the corporate tax with one embezzlement act. Therefore, there is room for double taxation, so related regulations need to be revised. KCI Citation Count: 0